IBA uptake and metabolism of different type of plum rootstocks hardwood cuttings - Sándor, Gergő (Acta Biologica Szegediensis, 2008)
The 50% alcoholic soluted 2000 ppm and 4000 ppm IBA (indole-3- butyric acid) uptake and the decomposition of IBA in the examined plum rootstock hardwood cuttings was determined by HPLC. ‘INRA Marianna’GF 8-1’, ‘Myrabalan B’, ‘MY-KL-A’, ‘INRA Saint Julien GF 655/2’, ‘Fehér besztercei’ plum rootstocks were used as plant material. The cuttings were collected on the 26 of October 2006, the basal parts IBA content was measured regularly by HPLC during the cold storage and rooting period. We found that all the cuttings was able to take up IBA and the 4000 ppm treatment cases double exogenous auxin level in the cuttings basal part parallel to the 2000 ppm. The uptake and decomposition of IBA by the myrobalan type ‘MY-KL-A’, ‘GF 8/1’ and ‘Myrobalan B’ rootstocks was the fastest, by others was slower, especially the ‘GF 655/2’. In the half-life of IBA in the basal parts of the hardwood cuttings we found large differences. The half decomposition took only two weeks at the myrobalana type rootstocks while in case of ‘Fehér besztercei’ it was more than 60 days.